The Relationship between nutritional status and menstrual cycle and anemia - Wijayanti, Lumastari Ajeng; Nurseskasatmata, Satria Eureka (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Introduction: Adolescence is a period of growth and puberty; adolescents are very concerned about appearance, so they pay attention to their diet until they are strict. This causes the intake needed to be unmet, then impacts the menstrual cycle and anemia. Objective: This study aims to analyze the relationship between nutritional status, the menstrual cycle, and the incidence of anemia in adolescent girls. Method: This research is an analytic observational study. The approach in this research is cross-sectional. The population is 447 female students aged 13-15; the sample is 83. Sampling using consecutive sampling. The data collection instrument used a questionnaire to determine the menstrual cycle, measure height and weight, and measure Hb levels with digital tools. Results: This study uses the Spearman Rank test formula value 0.05. The results of nutritional status with menstrual cycles were 0.016 < 0.05, and then significant results were obtained; on nutritional status with anemia, the results were 0.00 < 0.05, then substantial results were obtained, and the results of menstrual cycles with anemia were 0.06 > 0.05 then the result is not essential. Conclusion: It can be concluded that there is a relationship between nutritional status and the menstrual cycle and anaemia, but there is no relationship between the menstrual cycle and anaemia. Optimal nutritional status, including adequate iron intake, is essential for maintaining menstrual health and preventing anemia. Nutrition interventions and health education on the importance of balanced nutrition can be a practical step in supporting women's reproductive health